2019
DOI: 10.1073/pnas.1812453116
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic fMRI interrogation of brain-wide central vestibular pathways

Abstract: Blood oxygen level-dependent functional MRI (fMRI) constitutes a powerful neuroimaging technology to map brain-wide functions in response to specific sensory or cognitive tasks. However, fMRI mapping of the vestibular system, which is pivotal for our sense of balance, poses significant challenges. Physical constraints limit a subject’s ability to perform motion- and balance-related tasks inside the scanner, and current stimulation techniques within the scanner are nonspecific to delineate complex vestibular nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 68 publications
7
48
0
Order By: Relevance
“…Most of the significant regions in the hippocampus were in CA1, followed by CA2. This is consistent with animal studies that have shown evoked field potentials, increased single neuron discharge, increased activation using fMRI, and c-Fos activation – all in CA1 – following electrical activation of the peripheral vestibular system [ 6 , 12 , 63 , 69 , 70 ]. Moreover, several studies have shown that vestibular lesions result in loss of location-specific firing of place cells, which largely reside in CA1 [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most of the significant regions in the hippocampus were in CA1, followed by CA2. This is consistent with animal studies that have shown evoked field potentials, increased single neuron discharge, increased activation using fMRI, and c-Fos activation – all in CA1 – following electrical activation of the peripheral vestibular system [ 6 , 12 , 63 , 69 , 70 ]. Moreover, several studies have shown that vestibular lesions result in loss of location-specific firing of place cells, which largely reside in CA1 [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, the exact pathways through which the loss of vestibular function may affect cognition is unknown. Functional neuroimaging studies in healthy subjects have shown that vestibular stimulation activates a large multisensory cortical and subcortical network, which primarily includes the insula, temporo-parietal junction, somatosensory cortex, hippocampus, medial entorhinal cortex (ERC), several thalamic nuclei, and basal ganglia [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. One prior study found that poorer vestibular function in older adults was associated with significantly reduced hippocampal volumes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diminished metabolism was found in ipsilateral entorhinal, visual, and somatosensory cortical areas. This is in line with the concept of a reciprocal inhibitory interaction between the sensory systems, i.e., activation of the vestibular system by GVS and downregulation of the visual and somatosensory systems (52), and was recently supported by imaging data on multiple central vestibular pathways that exert "large-scale modulatory effects of the vestibular system on sensory processing" (53).…”
Section: Vestibular Stimulation Pre-vs Post-lesion (Paired T-test)supporting
confidence: 81%
“…This strategy allowed an optogenetic stimulation, followed by an electrophysiological response of PNS [41]. The vestibular system is controlled by neurons within the vestibular nucleus (VN), stimulating the auditory, visual, and motor centers [42]. Generally, through fMRI (functional magnetic resonance), brain functions are mapped in response to different sensory or cognitive tasks; however, fMRI does not work well in the studies on VN.…”
Section: Applications In Neurological Diseasesmentioning
confidence: 99%